Early Identification of Correlated Risk Factors can Improve the Prognosis of Patients with Postoperative Intracranial Infection - Zhang, Rongfang; Niu, Jiangtao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background In this retrospective study, we explore the clinical risk factors correlated to the prognosis of patients who suffered from central nervous system infection after a neurosurgical procedure.Methods The study included 113 patients diagnosed with a postoperative intracranial infection. Several factors with clinical relevance were identified and analyzed by univariate analyses. The risk factors that showed any significant difference between the cases were analyzed by multivariate logistic regression analyses.Results Here we show that the duration of the drainage before infection (measured in days; Beta [B]: –0.113; odds ratio [OR]: 0.893; 95% confidence interval [CI]: 0.805–0.991; p = 0.033), the number of antibiotics used for the treatment (B: –1.470; OR: 0.230; 95% CI: 0.072–0.738; p = 0.013), and the number of leucocytes in the cerebrospinal fluid (CSF; B: –0.016; OR: 0.984; 95% CI: 0.970–0.998; p = 0.027) are risk factors for the prognosis of patients with an intracranial infection. In contrast, the duration of antibiotic treatment (measured in days; B: 0.176; OR: 1.193; 95% CI: 1.063–1.339; p = 0.003) turned out to be a positive factor for recovery from infection.Conclusions Our results suggest that early identification of the correlated risk factors can improve the prognosis of patients with intracranial infection after neurosurgery.
Keywords: intracranial infection; neurosurgery; risk factors; prognosis